2019
DOI: 10.1115/1.4042485
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Decomposition-Enhanced Control for Point and Curved-Foot Planar Bipeds Experiencing Velocity Disturbances

Abstract: This paper extends the use of velocity decomposition of underactuated mechanical systems to the design of an enhanced hybrid zero dynamics (HZD)-based controller for biped robots. To reject velocity disturbances in the unactuated degree-of-freedom, a velocity decomposition-enhanced controller implements torso and leg offsets that are proportional to the error in the time derivative of the unactuated velocity. The offsets are layered on top of an HZD-based controller to preserve simplicity of implementation. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Thus, the nominal motion was defined as: where α k were the polynomial coefficients chosen to minimize a weighted torque-square objective function [ 10 ]. Because previous research indicated that speed has an impact on falls [ 15 , 21 , 22 , 46 ], three different nominal gaits from [ 10 ] were tested—slow (0.98 m/s), medium (1.30 m/s), and fast (1.56 m/s). The models associated with each gait were adult-sized, although each had somewhat different mass and length parameters because each gait was associated with a different person or group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the nominal motion was defined as: where α k were the polynomial coefficients chosen to minimize a weighted torque-square objective function [ 10 ]. Because previous research indicated that speed has an impact on falls [ 15 , 21 , 22 , 46 ], three different nominal gaits from [ 10 ] were tested—slow (0.98 m/s), medium (1.30 m/s), and fast (1.56 m/s). The models associated with each gait were adult-sized, although each had somewhat different mass and length parameters because each gait was associated with a different person or group.…”
Section: Methodsmentioning
confidence: 99%
“…One challenge with predicting falls is that they have many potential causes. Robotic studies have primarily evaluated falls due external factors, such as walking across uneven terrain [ 13 ] or due to velocity disturbances such as a push [ 14 , 15 ]. These works also tend to focus on discrete, rather than continuous, perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity decomposition-enhanced controller was also implemented on a three-link biped model with curved feet, which considerably reduced the energetic cost of walking relative to the point-foot case (Fevre et al, 2019). The velocity disturbance rejection performance of the velocity decomposition-enhanced controller on the curved-foot model was consistent with the point-foot model, and switching from one model to the other did not require re-tuning the controller gains.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…The velocity disturbance rejection performance of the velocity decomposition-enhanced controller on the curved-foot model was consistent with the point-foot model, and switching from one model to the other did not require re-tuning the controller gains. Moreover, the complexity of the proposed control strategy remains the same with the addition of curved feet (Fevre et al, 2019), which is another desirable aspect of low-level feedback controllers for extension to more complex biped robots.…”
Section: Simulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation